The Wiggles. Surfer Jeff [videorecording (DVD)] - Field, Anthony, 1963-; Cook, Murray, 1960-; Fatt, Jeff, 1954-; Page, Greg, 1972- (Distributed by NCircle Entertainment ], 2013)
"Join The Wiggles as they embark on their most exciting adventure ever! Jeff meets Gino the Genie who grants him three wishes! What does Jeff wish for from Gino? To see the world, of course! Jeff visits exotic locations such as Abu Dhabi, London, Rome, Paris and Sydney's Royal Botanic Garden! Dance along with The Wiggles as they perform songs from around the world. Surf's up! "--Container.